2019
DOI: 10.32014/2019.2518-1467.100
|View full text |Cite
|
Sign up to set email alerts
|

Foresight Innovations in Educational Systems in the Brics Countries

Abstract: Қазақстан Республикасы Ұлттық ғылым академиясы "ҚР ҰҒА Хабаршысы" ғылыми журналының Web of Science-тің жаңаланған нұсқасы Emerging Sources Citation Index-те индекстелуге қабылданғанын хабарлайды. Бұл индекстелу барысында Clarivate Analytics компаниясы журналды одан əрі the Science Citation Index Expanded, the Social Sciences Citation Index жəне the Arts & Humanities Citation Index-ке қабылдау мəселесін қарастыруда. Web of Science зерттеушілер, авторлар, баспашылар мен мекемелерге контент тереңдігі мен сапасын … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Researchers also note the role of special training activities for the prevention and correction of distress and activities for the application of methods of stress management and stress management assigned in the course of education and upbringing, including family, preschool, school, and university. Thus, they note the importance of implementing a health-preserving, psychologically safe, selfhealing, psychoecological approach to stressful situations, the importance of reflecting on what is happening, helping to preserve and restore the integrity (self) of an individual as a person, partner and professional [4]. Self-healing / self-healing techniques (self-clarification and self-harmonization) should be aimed at activating and building up a person's reserves, his health and stress resistance, and not just "waste".…”
Section: Research Results and Its Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also note the role of special training activities for the prevention and correction of distress and activities for the application of methods of stress management and stress management assigned in the course of education and upbringing, including family, preschool, school, and university. Thus, they note the importance of implementing a health-preserving, psychologically safe, selfhealing, psychoecological approach to stressful situations, the importance of reflecting on what is happening, helping to preserve and restore the integrity (self) of an individual as a person, partner and professional [4]. Self-healing / self-healing techniques (self-clarification and self-harmonization) should be aimed at activating and building up a person's reserves, his health and stress resistance, and not just "waste".…”
Section: Research Results and Its Discussionmentioning
confidence: 99%
“…Arpentieva and colleagues have shown that professional stress among teachers is often associated with "numerous educational reforms and toughening requirements for teachers" and other teachers. Modern teachers in completely different ways and to varying degrees withstand the significant professional and accompanying professional loads that fall on their lot due to various reasons [4,5]. They almost constantly go through situations oversaturated with conflicts, difficulties, stresses, often leading to crises of their personal, interpersonal and professional functioning.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of studies on the links between different areas of the cerebral cortex of patients with schizophrenia, epilepsy and endogenous depression, each of these diseases is characterized by a specific pattern of synchronicity of biopotentials. In patients with schizophrenia, the strength of the interaction between the hemispheres and between the frontal and parietal regions of the right hemisphere is reduced (Merrin et al, 1989;Norman et al, 1997, Aksarina et al, 2019. They also had reduced integration between the frontal and temporal regions, mostly on the left.…”
Section: Discussionmentioning
confidence: 99%
“…However, this concept received full coverage only after the release of the works of Murray. As part of his teaching on infantile forms of activity, a separate "urethral complex" is distinguished, which received the additional name "Icarus complex" (Badalov, Sumanov, & Galako, 2016;Murray, 1955;Wiklund, 1978;Aksarina et al, 2019). It includes the following signs: cathexes of fire, enuresis, and the desire for immortality, pronounced narcissism and high ambitions with low tolerance to frustration.…”
Section: Introductionmentioning
confidence: 99%